Circulating Regulatory T-Cells in Monoclonal Gammopathies of Uncertain Significance and Multiple Myeloma: In Search of a Role. (14th July 2016) - D'Arena, Giovanni; Rossi, Giovanni; Laurenti, Luca; Statuto, Teodora; D'Auria, Fiorella; Valvano, Luciana; Simeon, Vittorio; Giudice, Aldo; Innocenti, Idanna; De Feo, Vincenzo; Filosa, Rosanna; Musto, Pellegrino
Abstract : The frequency and function of regulatory T-cells (Tregs) in multiple myeloma (MM) are still matter of debate. The percentage and absolute number of circulating Tregs (CD4 + C D 25 + h i g h d e n s i t y C D 127 - / l o w d e n s i t y ) from 39 patients with untreated MM and 44 patients with monoclonal gammopathies of uncertain significance (MGUS) were tested and compared with 20 healthy subjects as controls. The mean percentage number of circulating Tregs was 2.1% ± 1.0 (range 0.75–6.1%) in MM patients; 2.1% ± 0.9 (range 0.3–4.4%) in MGUS; and 1.5% ± 0.4 (range 0.9–2.1%) in controls (p ns). Mean absolute number of Tregs was 36.3/ μ L ± 23.7 (range 6.7–149/ μ L) in MM; 38.8/ μ L ± 19.1 (range 4.3–87/ μ L) in MGUS; and 39.4/ μ L ± 12.5 (range 18–63/ μ L) in controls (p ns). After a median follow-up of 38 months, 5 MGUS and 2 smoldering MM (SMM) transformed into overt MM; however Tregs number did not predict this evolution. With respect to MM patients and after a median follow-up of 33 months, Tregs did not show any significant correlation with main clinical and laboratory characteristics. Finally, from a functional point of view, Tregs displayed an effective suppressor function, irrespective of disease status. This study indicates that the number of circulating Tregs does not differ in different monoclonal gammopathies and normal subjects and do not correlate with clinical features of MM.